2012
DOI: 10.1016/j.amjcard.2011.07.071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild, Asymptomatic Obstructive Sleep Apnea on Daytime Heart Rate Variability and Impedance Cardiography Measurements

Abstract: Dysregulation of autonomic nervous system dynamics is important in the pathophysiology of cardiovascular risk in obstructive sleep apnea (OSA). Heart rate variability (HRV) and impedance cardiography measures can estimate autonomic activity but have not gained traction clinically. We hypothesized that, even in a cohort of mild, asymptomatic OSA patients without overt cardiovascular disease, daytime HRV metrics and impedance cardiography measurements of pre-ejection period (PEP) would demonstrate increased symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…Our findings regarding the heart rate variability in patients with OSAS need to be considered in the light of findings of other researchers like Balachandran et al who studied heart rate variability (HRV) and even found evidence of decrease in cardiac vagal modulation in asymptomatic OSA subjects using time-domain and frequency-domain HRV indices 15 . They proposed conducting further studies to explore the possibility of using heart rate variability for the noninvasive screening of obese asymptomatic OSA patients before they develop overt cardiovascular disease 15 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our findings regarding the heart rate variability in patients with OSAS need to be considered in the light of findings of other researchers like Balachandran et al who studied heart rate variability (HRV) and even found evidence of decrease in cardiac vagal modulation in asymptomatic OSA subjects using time-domain and frequency-domain HRV indices 15 . They proposed conducting further studies to explore the possibility of using heart rate variability for the noninvasive screening of obese asymptomatic OSA patients before they develop overt cardiovascular disease 15 .…”
Section: Discussionmentioning
confidence: 93%
“…They proposed conducting further studies to explore the possibility of using heart rate variability for the noninvasive screening of obese asymptomatic OSA patients before they develop overt cardiovascular disease 15 . Narkiewicz et al even felt that there may be a link between the degree of alteration in cardiovascular variability and the severity of OSA 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HF power reflects the activity of parasympathetic nervous system activity, whereas LF power reflects a combination of sympathetic and parasympathetic activity [92,105]. OSA patients showed increased sympathetic and reduced vagal modulation of HRV in comparison with controls [2,4]. This symphato-vagal imbalance is modified with CPAP therapy; in OSA patients with hypertension CPAP administration reduced the LF power [11,114].…”
Section: Heart Rate Variability In Osa Patientsmentioning
confidence: 99%
“…Balachandran et al [22] used heart rate variability (HRV) and pre-ejection period (PEP) derived from ICG traces, to estimate autonomic activity. The hypothesis of their study was that even in a cohort of patients with mild, asymptomatic obstructive sleep apnoea without overt cardiovascular disease, daytime HRV metrics and ICG measurements of pre-ejection period would demonstrate increased sympathetic and decreased parasympathetic modulation compared to matched controls.…”
Section: Sleep Studiesmentioning
confidence: 99%